1988
DOI: 10.1520/jfs11953j
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Postmortem Interval Based on the Third Component of Complement (C3) Cleavage

Abstract: To estimate postmortem interval (PMI), the spontaneous conversion of the native third component of complement (C3) to its derived fragments in whole blood was studied by crossed immunoelectrophoresis. C3 cleavages in vitro at different temperatures showed that the incubation of whole blood at a higher temperature led to a faster conversion of beta 1C (native C3) to beta 1A (C3c). In cadaveric blood, we found a significant positive correlation between percentage of C3 cleavage and PMI. From these results, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…61 Some authors have proposed PMI estimation based on the effect of the PMI on protein concentrations. 8,[28][29][30]62,63 According to our results, the total protein concentration initially increased, up to 48 h, reaching a plateau that remains unchanged until the end of the experiment. The albumin concentration in vitro increased slightly up to 216 h and then decreased over the remaining putrefaction time.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…61 Some authors have proposed PMI estimation based on the effect of the PMI on protein concentrations. 8,[28][29][30]62,63 According to our results, the total protein concentration initially increased, up to 48 h, reaching a plateau that remains unchanged until the end of the experiment. The albumin concentration in vitro increased slightly up to 216 h and then decreased over the remaining putrefaction time.…”
Section: Discussionsupporting
confidence: 55%
“…The estimation of the PMI based on the third component of C3 cleavage was previously studied in postmortem blood, where a significant positive correlation between the percentage of C3 cleavage and PMI was found. 62 Additionally, we observed a decrease in the immunoglobulin G and M concentrations with the putrefaction time. However, the immunoglobulin A concentration remained practically constant up to 120 h, decreasing over the remaining time.…”
Section: Discussionmentioning
confidence: 64%
“…Kominato et al investigated the conversion of a complement factor (C3) to its constituent fragments in the blood for the determination of PMI by immune electrophoresis and suggested that there was a statistically significant correlation between C3 degradation and PMI, and thus, it was reported that PMI could be predicted by looking at the C3 fragmentation rate [24]. Endo et al measured monoamine metabolites in the cerebrospinal fluid and observed that the concentration of 3-4 dihydroxyphenylacetic acid increased with time after death and reported that it could be used in the determination of PMI [25].…”
Section: Role Of Biochemistry In the Estimation Of Death Timementioning
confidence: 99%
“…The methods mentioned in the above-mentioned literature generally remain as methods that are not used much in practice at the experimental level [1][2][3][22][23][24][25][26][27][28][29][30][31]. However, the question of the exact time of death remains on the documents pertaining to the autopsy request made by the prosecution offices.…”
Section: Why Do We Try To Estimate the Death Time?mentioning
confidence: 99%
See 1 more Smart Citation